Harnessing 3D Scanning and Printing Technology to Improve Students’ Proficiency in Assessing Foot Posture - Daniel R. Bonanno; Sheree E. Hurn; Helen A. Banwell; Daniel Alizzi; Hylton B. Menz (Journal of Foot and Ankle Research)
ABSTRACT Introduction The Foot Posture Index (FPI‐6), widely used to quantify foot posture, is a core component of musculoskeletal curricula in undergraduate podiatry programs. Teaching the FPI‐6 can be challenging but 3D foot models provide a controlled risk‐free way to practice, potentially reducing anxiety and increasing confidence. This study examined the effects of 3D foot models on podiatry students' confidence and anxiety when performing the FPI‐6 and compared their scores to experts. Methods Fifty podiatry students from three Australian universities used the FPI‐6 to score nine 3D printed foot models ranging from −11 (highly supinated) to +12 (highly pronated). Students' self‐confidence and anxiety were measured before and after exposure to the 3D foot models using a 10‐item self‐confidence questionnaire and the 27‐item Competitive State Anxiety Inventory‐2 (CSAI‐2). Changes in self‐confidence were analysed with paired t‐tests, whereas median differences in CSAI‐2 scores pre‐ and post‐intervention were assessed using the Wilcoxon signed‐rank test. Students' foot posture scores were compared to consensus scores from an expert panel (n = 4) with variability in agreement explored using the Bland–Altman limits of agreement (LoA) analysis. Results Student confidence improved across all 10 questionnaire items after the FPI‐6 simulation with 3D foot models (p ≤ 0.015) with a mean increase of 8.6% across all items (range, 1.9%–11.6%) and medium to large effect sizes (Cohen's d = 0.44–0.94). On the CSAI‐2, 22 of 27 items showed improvements in cognitive and somatic state anxiety or self‐confidence (p ≤ 0.038), whereas five items showed no significant change. The Bland–Altman analysis revealed a small mean difference of 0.389 between student and expert consensus scores with 95% LoA ranging from −3.3 to 4.1. Conclusion The use of 3D foot models for FPI‐6 simulation enhances podiatry students' confidence and reduces anxiety. Student's foot posture scores had good overall agreement with expert scores, though some discrepancies remained. This highlights the value of pre‐scored models for targeted practice and emphasises the importance of validation and feedback to ensure confidence aligns with accuracy. The models demonstrated high utility, harnessing 3D scanning and printing technology to enhance students' proficiency in assessing foot posture.